Potential evapotranspiration estimation and its effect on hydrological model response at the Nong Son Basin - Nghi, Vu Van; Dung, Do Duc; Lam, Dang Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 4, 2008)
Abstract